Youth Employment : A Human Development Agenda for the Next Decade - Robalino, David; Margolis, David; Rother, Friederike; Newhouse, David; Lundberg, Mattias (World Bank, Washington, DC, 2014)
This paper reviews the main challenges facing countries in attempting to improve labor market outcomes among youth, focusing on the issues that became starkly visible during the recent financial crisis. In order to better identify and set up human development interventions, the paper proposes an agenda that focuses on three areas: (1) improving the understanding of the causes and consequences of poor labor market outcomes for youth; (2) continuing to learn from the evaluation of pilots and programs that aim to promote productive employment among young people; and (3) addressing implementation issues which frequently overwhelm the best designs. The paper utilizes research on youth employment to take stock of youth labor market outcomes across regions, focusing on inactivity, unemployment, and employment indicators. A review of what is known about current interventions, including those that appear in the youth employment Inventory database of programs, provides the basis for determining the efficacy of five categories of intervention: (i) skills training (including vocational training, on-the-job-training programs, literacy and numeracy programs, second-chance and equivalency programs, and soft-skills programs); (ii) entrepreneurship promotion (financial assistance, technical assistance, and entrepreneurship training); (iii) subsidized employment (including wage subsidy programs, public works, and public/community service programs); (iv) employment services (including search assistance and access to labor market information, job counseling and placement services, and financial assistance for job search); and (v) reforms to labor market regulation (including anti-discrimination legislation) training programs, wage subsidies. Finally, the paper proposes an agenda for research and policy analysis in the area of human development that is expected to help both deepen the understanding of youth employment issues and improve the selection, design, and implementation of youth employment programs.